Obtenção e caracterização de uma nova dispersão sólida de dapsona utilizando o ácido oxálico como coformador - BEZERRA , Raychimam Douglas Santana (2019)
Dapsone (DPS) is an oral antibiotic used to treat diseases caused by mycobacteria, such as tuberculosis and leprosy. It belongs to Class II of the Biopharmaceutical Classification System because it has low water solubility. This fact contributes to the reduction of its bioavailability and its therapeutic efficacy. Synthesis of novel solid drug dispersions, such as co-amorphous, has been a highly feasible alternative for improving the physico-chemical properties of drugs, such as increased water solubility. Thus, this work aimed to obtain and characterize a new DPS co-amorphous using oxalic acid (OXA) as a coforming agent. This solid dispersion was obtained using slow evaporation of the solvent. For this purpose, masses of DPS and OXA were weighed in order to obtain a binary mixture in the molar ratio of 1.0:1.5. This mixture was solubilized in 20 mL methanol and the solution allowed to stand at 40 ± 1 °C until complete evaporation of the solvent (about three days). For comparison purposes, the starting compounds (DPS and OXA) were individually recrystallized by the same method of obtaining the co-amorphous. The interaction stoichiometry between DPS and OXA was also investigated from the preparation of their binary mixtures in different molar ratios. Subsequently, the starting compounds, their binary mixtures and the co-amorphous DPS-OXA (1.0:1.5) were characterized by Powder X-ray Diffraction (PXRD), Fourier Transform Infrared Spectroscopy (FTIR) and Raman Spectroscopy, Thermogravimetry, Derivative Thermogravimetry and Differential Thermal Analysis (TG / DTG-DTA) and Differential Scanning Calorimetry (DSC). Stability studies of the amorphous phase by DRXP and solubility were also performed. The results obtained by DRXP confirmed the formation of an amorphous material for DPS-OXA (1.0:1.5) and was stable for at least 150 days. FTIR spectrum harvested for the co-amorphous showed bands displacement related to the sulfonyl group and amine group vibrations found in the DPS for higher wave numbers, and also a reduction in the intensity of the (–OH) vibrations present in the carboxyl group of the OXA.rec, such modifications indicate the interaction by means of such groups in the formation of the co-amorphous. Results by Raman Spectroscopy showed the disappearance of bands of the network vibrational modes, since the new amorphous material is devoid of crystalline lattice, we can observe the absence of the ν(C=O) stretch of the carboxyl group of OXA and displacement of the band corresponding to the sulphonyl group, νs(SO2) of DPS, indicating the performance of these groups in the interaction between DPS and OXA in the formation of co-amorphous. TG / DTG-DTA curves for the material obtained in this study show the absence of a fusion event in addition to any other event presented by DPS and OXA compounds. DSC curve recorded a glass transition temperature of 73 °C. Dissolution test showed that the DPS present in the co-amorphous DPS-OXA (1.0:1.5) is 5.4 times more soluble than the pure drug. Thus, the results present in this study confirmed the formation of unpublished co-amorphous DPS using OXA as a co-formulator in the 1.0:1.5 molar ratio. This new material has promising features such as good stability and greater solubility, requirements that can give DPS greater bioavailability by increasing its therapeutic efficacy by reducing the side effects of this drug in the treatment of leprosy.